Evaluation of Service Quality, Prices, and Product Variants towards Customer Loyalty through Brand Image during the Covid-19 Pandemic Era - Yayu Permatasari; Otto Randa Payangan; Andi Nur Baumassepe (Magister Management, Hasanuddin University, 2021)
This study aims to examine the effect of service quality, price and product variants on customer loyalty through brand image as an intervening variable for pharmacy customers in Sidrap Regency during the Covid-19 pandemic. The sample is determined using a purposive sampling technique (determination with certain considerations). Respondents in this study amounted to 100 respondents from the results of calculations using the Slovenian formula. The data was collected using a questionnaire that was sent online to the people of Sidrap Regency. The questions posed in the questionnaire use a linkert scale 1-5 then the data obtained is tested using validity tests, reliability tests, normality tests and regression tests where the data is carried out using the application statistical program version 21. Product and service solution application (SPSS) . To test the mediation (intervening), the method of path analysis (path analysis) is used. The results showed that service quality, price and service variants had a positive and significant effect on the brand image of service quality, prices and product variants which had a positive and significant effect on loyalty, brand image could not mediate the effect of service quality and price on customer loyalty, while brand image can mediate the effect of product variants on customer loyalty.